Transposons passively and actively contribute to evolution of the two-speed genome of a fungal pathogen - Faino, Luigi; Seidl, Michael F.; Shi-Kunne, Xiaoqian; Pauper, Marc; van den Berg, Grardy C.M.; Wittenberg, Alexander H.J.; Thomma, Bart P.H.J.

(untitled) (Genome Research, 2016)
Genomic plasticity enables adaptation to changing environments, which is especially relevant for pathogens that engage in “arms races” with their hosts. In many pathogens, genes mediating virulence cluster in highly variable, transposon-rich, physically distinct genomic compartments. However, understanding of the evolution of these compartments, and the role of transposons therein, remains limited. Here, we show that transposons are the major driving force for adaptive genome evolution in the fungal plant pathogen Verticillium dahliae. We show that highly variable lineage-specific (LS) regions evolved by genomic rearrangements that are mediated by erroneous double-strand repair, often utilizing transposons. We furthermore show that recent genetic duplications are enhanced in LS regions, against an older episode of duplication events. Finally, LS regions are enriched in active transposons, which contribute to local genome plasticity. Thus, we provide evidence for genome shaping by transposons, both in an active and passive manner, which impacts the evolution of pathogen virulence.